54 Effects of an injectable zinc solution at weaning as an alternative castration method during the backgrounding period in beef bulls. (28th November 2020) - Cauble, Reagan N; Powell, Powell G; Kegley, Elizabeth; Gadberry, Shane; Beck, Paul A; Sims, Michael; Shelton, Cody
Abstract: Castration is a routine management practice performed on an estimated 15 million bull calves each year in the United States. Although castration is a common practice worldwide, the process causes pain and stress that temporarily reduces performance. The objective of our study was to investigate the effects of a novel injectable zinc solution as an alternative castration method on the growth performance, testicular width, and serum testosterone concentrations of weaned beef bulls. Calves (n = 74) were processed at birth and were randomly assigned to 1 of 2 castration methods: 1) negative control, in which calves were surgically castrated at birth, or 2) chemically castrated, in which calves remained intact males until weaning and were chemically castrated with a 1 mL intratesticular injection of zinc solution in each testicle. Data were analyzed using the MIXED procedures of SAS and significance was declared at P < 0.05. Chemically castrated calves were heavier (P < 0.01) throughout the 168-d backgrounding phase compared to steers (285 and 266 kg respectively); however, the overall change in BW (P = 0.73) and ADG (P = 0.81) was similar between castration techniques. Testicular width measurements were greatest on d 28 and returned to baseline weaning measurements by d 56. Testicular width continued to decrease on d 77 and remained constant for the remainder of the backgrounding period (time P < 0.01). Although testicular width decreased, chemically castrating did not affect (time P = 0.17) testosterone concentrations; however, concentrations were numerically lowest on d 28 and 56. Chemically castrating cattle at weaning resulted in greater overall body weights and reduced testicular width during the backgrounding period; however, it did not eliminate testosterone production as compared to surgically castrating at birth. This solution was not effective in bulls at weaning.